Bioinformatics analysis to investigate the potential relationship between mitochondrial structure and function-related genes and the immune microenvironment in atherosclerosis - Yang, Hanning; Sun, Yue; Li, Shumin; Tang, Yueyue; Wang, Yuxue; Li, Yunyan; Lu, Yongping (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aims to elucidate the interactions between genes associated with mitochondrial structure and function and the immune microenvironment in atherosclerosis.MethodsDifferentially expressed mitochondria-related genes (DE-MRGs) were identified through the analysis of two gene expression datasets, GSE100927 and GSE159677, in conjunction with a list of mitochondria-related genes sourced from the MitoCarta3.0 database. The immune profile of infiltrating immune cells in atherosclerotic carotid artery (CA) patients compared to controls (CTLs) was assessed using CIBERSORT. Potential target genes were screened based on Spearman correlation analysis between specific DE-MRGs and differentially expressed immune cells. Furthermore, the correlation between characterized DE-MRGs and immune cells in AS was examined at the single-cell level, and the expression of key genes was validated in vitro.ResultsOur study identified a robust association between four key genes—C15orf48, UCP2, PPIF, and MGST1—among 15 DE-MRGs, and immune macrophage polarization. These genes exhibited alterations corresponding to the degree of macrophage differentiation in AS. Additionally, Gene Set Enrichment Analysis (GSEA) revealed that C15orf48, UCP2, PPIF, and MGST1 modulate multiple immune pathways within the body. The mRNA expression levels of these four key genes in AS were confirmed via quantitative real-time PCR (qRT-PCR), with results aligning with bioinformatics predictions. Compared to the control group, the expression levels of C15orf48, UCP2, and PPIF were significantly elevated in AS macrophages, whereas MGST1 expression was notably reduced in AS macrophages. Consequently, these mitochondria-related genes—C15orf48, UCP2, PPIF, and MGST1—may influence the immune microenvironment in AS by modulating macrophage differentiation.ConclusionC15orf48, UCP2, PPIF, and MGST1 may serve as potential therapeutic targets for enhancing the atherosclerotic immune microenvironment in future interventions.